2015
DOI: 10.1093/hmg/ddv039
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-coupled RNA surveillance in human genetic diseases caused by splice site mutations

Abstract: Current estimates indicate that approximately one-third of all disease-causing mutations are expected to disrupt splicing. Abnormal splicing often leads to disruption of the reading frame with introduction of a premature termination codon (PTC) that targets the mRNA for degradation in the cytoplasm by nonsense mediated decay (NMD). In addition to NMD there are RNA surveillance mechanisms that act in the nucleus while transcripts are still associated with the chromatin template. However, the significance of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…These exons often introduce premature termination codons (PTCs) into the resulting transcripts, which can target them for nonsense-mediated decay (NMD) in the cytoplasm3335 (Figure 1A). In some cases, abnormal splicing also leads to transcription-coupled surveillance mechanisms that can decrease the expression of resulting transcripts36. These quality control pathways often decrease the expression of transcripts containing cryptic exons, which makes these exons more difficult to detect and annotate during transcriptome sequencing analysis610.…”
Section: Types Of Non-canonical Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…These exons often introduce premature termination codons (PTCs) into the resulting transcripts, which can target them for nonsense-mediated decay (NMD) in the cytoplasm3335 (Figure 1A). In some cases, abnormal splicing also leads to transcription-coupled surveillance mechanisms that can decrease the expression of resulting transcripts36. These quality control pathways often decrease the expression of transcripts containing cryptic exons, which makes these exons more difficult to detect and annotate during transcriptome sequencing analysis610.…”
Section: Types Of Non-canonical Splicingmentioning
confidence: 99%
“…Therefore, genome-wide sequencing will be required to reveal the full range of intronic variation that can activate cryptic splicing, perturb distal branch points or disturb regulatory regions32. It is also important to bear in mind that abnormally processed pre-mRNAs can interfere with transcription or cause co-transcriptional decay36,180. Dedicated genomic and transcriptomic experiments and computational approaches will therefore be needed to detect the full range of mutations that cause disease via non-canonical splicing.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…More than 200 human diseases, including progeria and some forms of breast cancer and cystic fibrosis, are caused by point mutations that affect pre-mRNA splicing by destroying or weakening splice sites, or activating cryptic ones ( Wang et al, 2012 ), thereby producing mRNAs that encode defective proteins or that are targets for nonsense-mediated mRNA decay (NMD). Splicing defects can also lead to the cotranscriptional degradation of nascent pre-mRNAs ( Davidson et al, 2012 ; Vaz-Drago et al, 2015 ). A splice site mutation in BRAF is associated with resistance to the anticancer agent vemurafenib, but inhibitors of the generic splicing factor SF3B1 decrease the production of the mutation-induced BRAF variant and inhibit drug-resistant cell proliferation ( Poulikakos et al, 2011 ; Salton et al, 2015 ).…”
Section: Shooting the Pre-messenger By Disrupting Splicing Control Elmentioning
confidence: 99%
“…That study also found that sQTLs were enriched in regions of the histone modification H3K4me3, a marker of gene promoters. Gene transcription and post‐transcriptional processing are coupled and factors that influence transcription can influence exon usage . These factors include the rate of RNA polymerase II elongation and chromatin structure and histone modifications that alter transcription rates .…”
Section: Genome‐wide Predictions Of Genetic Variants and Alternative mentioning
confidence: 99%